2018
DOI: 10.1111/eth.12751
|View full text |Cite
|
Sign up to set email alerts
|

Female nursery web spiders (Pisaurina mira) benefit from consuming their mate

Abstract: The often coincidental involvement of cooperation and conflict in animal reproduction is epitomized by sexual cannibalism, which can lead to obvious male costs while simultaneously providing direct benefits to developing offspring. Male nursery web spiders (Pisaurina mira) avoid postcopulatory sexual cannibalism by wrapping females with silk. Here, we test the hypothesis that this silk wrapping results in a loss of consumption cost for females. In specific, we hypothesize that females lose out on potential fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…TEM micrographs of purified nanoparticles produced by P. rhodesiae were obtained using the same microscope. Then, the size of NPs was determined using the Pixelstick software (Plum Amazing Software LLC, Princeville, HI, USA) to establish a size-frequency histogram [ 45 , 46 ]…”
Section: Methodsmentioning
confidence: 99%
“…TEM micrographs of purified nanoparticles produced by P. rhodesiae were obtained using the same microscope. Then, the size of NPs was determined using the Pixelstick software (Plum Amazing Software LLC, Princeville, HI, USA) to establish a size-frequency histogram [ 45 , 46 ]…”
Section: Methodsmentioning
confidence: 99%
“…Or does it benefit females in some manner? In addition to instances of female ''catalepsy'' during mating, males of some spider species, such as the nursery-web spider Pisaurina mira (Walckenaer, 1837) reduce their likelihood of being cannibalized by physically restraining their female partners with silk during sperm transfer (Anderson & Hebets 2018). A series of behavioral studies on this system have revealed a benefit to males of silk-wrapping as well as a lost opportunity cost for females (Anderson & Hebets 2016, 2017Scott et al 2018).…”
mentioning
confidence: 99%